A series of mixed-ligand 2D and 3D coordination polymers assembled from a novel multifunctional pyridine-tricarboxylate building block: hydrothermal syntheses, structural and topological diversity, and magnetic and luminescent properties1. Issue 96 (17th October 2015) - Gu, Jin-Zhong; Cui, Yan-Hui; Wu, Jiang; Kirillov, Alexander M.
<x xml:space="preserve">Abstract</x> 4-(5-Carboxypyridin-2-yl)isophthalic acid (H3L) was applied as a new principal building block for the self-assembly generation of mixed-ligand coordination polymers.